2013
DOI: 10.1128/aem.03067-12
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Relationships of Vibrio parahaemolyticus Isolates from Clinical, Human Carrier, and Environmental Sources in Thailand, Determined by Multilocus Sequence Analysis

Abstract: e Vibrio parahaemolyticus is a seafood-borne pathogenic bacterium that is a major cause of gastroenteritis worldwide. We investigated the genetic and evolutionary relationships of 101 V. parahaemolyticus isolates originating from clinical, human carrier, and various environmental and seafood production sources in Thailand using multilocus sequence analysis. The isolates were recovered from clinical samples (n ‫؍‬ 15), healthy human carriers (n ‫؍‬ 18), various types of fresh seafood (n ‫؍‬ 18), frozen shrimp (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
44
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 63 publications
9
44
0
1
Order By: Relevance
“…These observations correspond to previous investigations and are typical for epidemic populations [13,15,23,24,27]. In these populations clones emerge from a background of recombinogetic bacteria occasionally and are able to spread [53].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These observations correspond to previous investigations and are typical for epidemic populations [13,15,23,24,27]. In these populations clones emerge from a background of recombinogetic bacteria occasionally and are able to spread [53].…”
Section: Discussionsupporting
confidence: 90%
“…[24]. These pSTs represent a large number of different STs of various geographic origins (pST1 corresponds to 142 STs and pST2 to 127 STs).…”
Section: Discussionmentioning
confidence: 99%
“…Interspecies recombination at atpD and rpoD loci was also detected in our data set for strains belonging to pathovars guizotiae and populi, respectively. The occurrence of interspecies homologous recombination at housekeeping gene loci was previously revealed in other bacterial species (78,79). Our data support a predominant role of intra-and interspecies recombination in shaping the genetic diversity of X. arboricola.…”
Section: Discussionsupporting
confidence: 73%
“…Terai et al (1991) hypothesize that the tdh ancestor gene would probably originate in V. hollisae and spread to some strain of o ther environmental Vi brionaceae, as V. parahaemolyticus, V. cholerae non-O1, and V. mimicus, probably via an insertion sequence. Moreover, according to Theethakaew et al (2013), the presence of different haemolysin gene profiles within V. parahaemolyticus, accounts for horizontal gene transfers events involving both the tdh and trh encoding genes. The presence of tdh and trh negative isolates within V. parahaemolyticus is actually quite common in the environment (Robert-Pillot et al 2004;Ceccarelli et al 2013) and have been also found in clinical samples (Haley et al 2014).…”
Section: Occurrence Of Virulence-associated Genes In the Vibrio Isolatesmentioning
confidence: 99%